Next-generation ARIA care pathways for rhinitis and asthma: a model for multimorbid chronic diseases - Bousquet, J Jean (2019)
In all societies, the burden and cost of allergic and chronic respiratory diseases are increasing rapidly. Most economies are struggling to deliver modern health care effectively. There is a need to support the transformation of the health care system into integrated care with organizational health literacy.